2020
DOI: 10.1186/s13018-020-01958-2
|View full text |Cite
|
Sign up to set email alerts
|

The choice of screw internal fixation and hemiarthroplasty in the treatment of femoral neck fractures in the elderly: a meta-analysis

Abstract: Background Femoral neck fractures are common fractures in the elderly. Common treatment options include internal fixation (IF) and hemiarthroplasty (HA). However, the clinical application of these two options is always controversial due to the potential clinical trauma, postoperative function, early complications, and other factors. Materials and methods Randomized controlled trials and cohort studies comparing screw fixation and hemiarthroplasty in elderly patients with displaced femoral neck fractures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(51 reference statements)
1
9
0
1
Order By: Relevance
“…Indeed, delirium in elderly patients with FNF should be monitored more carefully. Mortality rate at 1 year was not different after MSF and cementless BHA in each group (p > 0.05) and compatible with the findings of previous studies 38 , 39 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, delirium in elderly patients with FNF should be monitored more carefully. Mortality rate at 1 year was not different after MSF and cementless BHA in each group (p > 0.05) and compatible with the findings of previous studies 38 , 39 .…”
Section: Discussionsupporting
confidence: 91%
“…In 2019, Pulkit Jain et al [29] concluded in their study that though unipolar AMP faces criticism for acetabular wear, most patients showed excellent to good results and is a good choice in geriatric patients. In 2020, Cui et al [30] in their meta-analysis of 7 randomized controlled trials and five cohort studies, concluded that in the treatment of elderly femoral neck fractures, the internal fixation group has lesser operative time and less bleeding, and the perioperative advantage is more pronounced. However, the Hemi-replacement group had more advantages in postoperative functional scoring and reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…These patients who undergo replacement arthroplasty will be able to weight-bear immediately postoperatively. In contrast to patients who are on non-weight bearing order post-operatively, patients who mobilize early demonstrate an additional functional benefit [13,14]. Besides that, early weight-bearing after replacement arthroplasty has an additional benefit in increasing bone density [14].…”
Section: Figure 4: Pelvic Plain Radiographs Of the Patient In Case 3 Show Nonunion Of Right Neck Of Femur (Nof) Fracture And Non-displacementioning
confidence: 99%
“…In contrast to patients who are on non-weight bearing order post-operatively, patients who mobilize early demonstrate an additional functional benefit [13,14]. Besides that, early weight-bearing after replacement arthroplasty has an additional benefit in increasing bone density [14]. In ESRD patients with reduced life expectancy, the quality of life after replacement arthroplasty will be of utmost priority when they unfortunately suffer from NOF fractures [15].…”
Section: Figure 4: Pelvic Plain Radiographs Of the Patient In Case 3 Show Nonunion Of Right Neck Of Femur (Nof) Fracture And Non-displacementioning
confidence: 99%